The influence of maize density on resource use and productivity: an experimental and simulation study - Jagtap, S.S.; Alabi, R.T.; Adeleye, O. (1998)
Maize productivity relationships were studied at Ibadan in the derived savanna of south-western Nigeria using the CERES-Maize simulation model at six crop densities ranging from 2.96 to 13.3 plants m-2. The absolute growth rate for all plant components decreased linearly with density. The optimum density was highest for LAI, 9.35 plants m-2, and lowest for grain yield, 6.95 plants m-2. The mean absolute error in model predictions were 1.8% for days to silking and maturity, 8% for LAI, 5% for total dry matter and 13% for ear yield. Measured LAI, tops and ear weights across all densities were related to simulation outputs using: LAIM = 1.23 LAIs-0.58, R2= 0.70; TOPM= 0.49 TOPs +3154, R2=0.30; and EARM=1.04 EARs-150, R2=0.90. The model simulation of ear weight at densities greater than 8.89 plants m-2 was unacceptable. Although simple and easy, the use of the CERES-Maize model in sub-Saharan Africa may be limited due to access to daily weather data, detailed soil data and computers. Using the simulated outputs as inputs, second order polynomials with density as the independent variable were fitted to the data to develop summary models that are more accessible in an intellectual and practical sense. These summary models may be used in the economic analysis of maize production.